Comparative Study of the Cure Characteristics and Mechanical Properties of Natural Rubber Filled With Different Calcium Carbonate Resources. Issue 3 (12th November 2019) - El Mogy, Soma A.; Darwish, N. A.; Awad, A.
Abstract : Bio‐waste materials such as eggshell (ES) and fishbone (FB) were used as new fillers compared with commercial calcium carbonate (CC) in natural rubber composite. The effect of their presence in the rubber mix on the rheometric study, morphology, mechanical properties, hardness, and abrasion resistance has been investigated at constant filler content (30 phr). The filler and their composites were characterized by Fourier‐transform infrared, X‐ray diffraction, thermogravimetric analysis, and scanning electron microscope (SEM). The results showed that the cure time and scorch time of the composites filled with CC and ES are lower than the composites filled FB filler. On the other hand, composites with ES and CC showed enhanced values of tensile, modulus at 100% and 300% elongation, hardness, and abrasion resistance. The morphological data revealed that CC and ES fillers are better dispersed in the rubber matrix than FB filler. J. VINYL ADDIT. TECHNOL., 26:309–315, 2020. © 2019 Society of Plastics Engineers